Local therapy for cancer therapy-associated uveitis: a case series and review of the literature. Issue 5 (13th August 2019) - Venkat, Arthi Ganesh; Arepalli, Sruthi; Sharma, Sumit; Karthik, Naveen; Lowder, Careen; Ehlers, Justis P; Singh, Arun; Goshe, Jeffrey; Srivastava, Sunil
Abstract : Background/aims: Immunotherapy and targeted therapy for metastatic cancer may cause immune-related adverse events (irAEs) such as uveitis. If irAEs are severe or require systemic steroids, cancer therapy is often held or discontinued. Local steroid therapy for cancer therapy-associated uveitis allows the continuation of cancer therapy. This series demonstrates successful management of cancer therapy-associated uveitis with local therapy based on uveitis subtype. Methods: This is an Institutional Review Board-approved retrospective case series of patients with uveitis secondary to immunotherapy or targeted therapy managed with local treatment, and focused literature review. Results: Five patients (median age: 54, range 31 to 75) were included. Time to uveitis onset following cancer therapy initiation was 3 to 12 months. All patients received checkpoint inhibitor therapy; one patient additionally received targeted therapy. Two patients presented with anterior uveitis, two with panuveitis and one with posterior uveitis. Four of five patients demonstrated evidence of posterior segment inflammation on multimodal imaging. Anterior uveitis was successfully treated with topical prednisolone acetate 1% (PA 1%) alone, and posterior segment involvement recalcitrant to topical PA 1% was treated successfully with topical difluprednate, intravitreal triamcinolone acetonide or a combination. Patients with isolated anterior uveitis did not require maintenance topical therapy; those with posterior and panuveitis required chronic low-dose topical therapy. Conclusion: Based on our series as well as the existing literature demonstrating the use of local therapy for irAEs, we propose an approach to local therapy for cancer therapy-associated uveitis starting with topical steroids and initiating injectable steroids in cases of recalcitrant panuveitis or posterior uveitis. Subclinical inflammation on posterior segment imaging responds robustly to difluprednate or intravitreal steroid therapy, and patients with posterior segment involvement may require more aggressive management and long-term maintenance.